Application of Synthetic Analytic Assisted Structural Methods of Linguistic Encyclopedia to Improve Early Reading Skills of Elementary School Students - Setiawan, Dwi Agus; Windasari, Eka Betty; Sunarti, Aris Sri (Actual Insight, 2025)
This Classroom Action Research aims to improve the initial reading skills of grade II students at Tanjungrejo 1 Malang Public Elementary School through the implementation of the Structural Analytic Synthetic (SAS) method assisted by an encyclopedia. The SAS method was selected because it emphasizes learning to read by starting with whole sentences, which are then analyzed into words and syllables before being resynthesized. This approach is considered effective in helping students understand the overall structure of language and develop reading fluency. This research applied the Classroom Action Research design following the Kemmis and McTaggart model, implemented in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The data collection techniques included observation sheets for teacher and student activities, interview guidelines, documentation, and reading skills tests designed to assess students' abilities in recognizing letters, syllables, and comprehending texts. The results showed an improvement in students' initial reading skills, increasing from 64% in the pre-action stage to 75% in Cycle I, and further to 88% in Cycle II. Additionally, students demonstrated increased enthusiasm, participation, and motivation in learning to read. These findings indicate that the implementation of the encyclopedia-assisted SAS method is effective in enhancing students' early reading skills and creating a more engaging and meaningful learning environment.